Public sector accounting reform in Latin America and Epistemic Communities: an institutional approach - Fabrício Ramos Neves; Mauricio Gómez-Villegas (Revista de Administração Pública, 2020)
Abstract Latin American countries have undergone a growing interest in international accounting standards. Several countries are making progress in the adoption of international standards driven by different internal factors as well as external dynamics. The role of experts in the design of public policies associated with international standards has been studied by the epistemic community theory, which is the theoretical framework used in this study to address the influence of different international organizations on the adoption of IPSAS in Brazil and Colombia. This paper discusses the isomorphic institutional pressure exerted over the governments of these two countries in order to meet an international standard considered to be adequate. Meanwhile, the emerging trend towards the adoption of IPSAS in Latin America continues to grow, although some obstacles to achieving the goals defined in the reform arise.